Prevalence of zoonoses found in cattle slaughtered in the State of Sao Paulo between 2005 and 20151 - Ortunho, Vanessa Veronese [UNESP]; Bonilha Pinheiro, Rafael Silvio [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2018)
In Brasil is known that zoonosis are diseases that could be present in flock, being causes of condemnation and underutilization of carcasses, but few studies goal the prevalence of these diseases. The objective of this study was to identify the zoonosis found in bovine carcasses slaughtered in the State of Sao Paulo between 2005 and 2015, to determine the prevalence of these diseases and to estimate the injury they caused when the total condenation. In this experiment were found brucellosis, cysticercosis, fasciolosis, hydatidosis, sarcosporidiosis and tuberculosis. Cysticercosis has been shown to be the most prevalent pathology and to less sarcosporidiosis. The damage caused by the carcasses was totally condemned was U$ 64,032,654.61; value of the dollar obtained on January 31, 2015.
Keywords: carcasses; cattle breeding; epidemiology; prevention; public health